Broth recycling in high carbon demanding single cell oil fermentation increased the product to effluent generation ratio. (December 2018) - Diwan, Batul; Gupta, Pratima
Graphical abstract: Highlights: Prospect of fermentation broth recycle for reducing freshwater dissipation has been studied. SCO production via oleaginous isolates was selected as a fermentation model. Non detoxified rice straw hydrolysate was used as an inexpensive substrate. Work elucidates 100% supernatant broth recycle without sugar supplementation for the first time. Broth served as an effective substrate for SCO production till two successive fermentation cycles. Abstract: In the attempt to minimize the incessant rise in industrial effluent discharge and maximize the existing resource utilization, present work demonstrates a proof of concept study on recycling of Single cell oil (SCO) fermentation effluent. To offset the high production cost associated with SCO fermentation, saccharified rice straw was utilized as cheap fermentable carbon (C) source. Fermentation broth formulated from Non-detoxified Liquid hydrolysate (NDLH) of rice straw(C: 50 g/l), was recycled without any dilution and carbon supplementation (mimicking a fermentation effluent) for two subsequent rounds to culture indigenous oleaginous yeast isolates NBT-8 and NBT-13. The resultant lipid titers in three consecutive fermentations were 1.036 g/l, 0.546 g/l, and 0.34 g/l from NBT-13 while 1.2 g/l, 0.96 g/l and 0.57 g/l from NBT-8 respectively. It was noteworthy that even at 100% recycle ratio, the NDLH based broth served as effective inexpensive substrate for NBT-8 up to two subsequent cycles resulting in good cumulative lipid titer of 2.16 g/l.